Rice residue management in wheat under different tillage practices and nitrogen doses - Kumar, Arvind; Jat, M.L.; Kumar, Ashok; Tomar, Jaibir; Kumar, Sudhir; Kushwaha, S.R. (Annals of Agricultural Research, 2016)
A field experiment on sandy loam was conducted during rabi 2005-06 and 2006-07 at the research farm of the Janta Vedic (P.G.) College, Baraut, district-Baghpat (U.P.) to study the growth, yield and economics of wheat (Triticum aestivum L.) under different rice residue and zero and conventional tillage practices in main plots and four nitrogen levels (0, 50 kg, 100 kg and 150 kg N/ha) in sub plots replicated crops. Residue retained with zero tillage recorded significantly higher yield attributes as well as grain and straw yield over other residue and tillage management. The increasing rate of nitrogen at higher dose (150 kg N/ha and 100 kg N/ha) produced significantly higher grain weight/ spike as compared to 50 kg N/ha application. The higher rates of nitrogen application showed significantly better grain and straw yield as compared to lower levels of nitrogen application. Net return (Rs. 31,865 and 30,126 Rs /ha) and B:C ratio (1.94 and 1.75) were also recorded maximum under residue retained with zero tillage during 2005-06 and 2006-07, respectively. The higher rate of nitrogen (150 kg N/ha) gave higher net profit (35,272 and 33,604 Rs/ha), highest B:C ratio (1.86 and 1.69) during respective years.